Precious metal clusters as fundamental agents in bioimaging usability - He, Xiaoxiao; Liu, Shaojun; Hu, Xi; Huang, Xiongyi; Zhang, Hehua; Mao, Xiang (Frontiers in Chemistry, 2023)
Fluorescent nanomaterials (NMs) are widely used in imaging techniques in biomedical research. Especially in bioimaging systems, the rapid development of imaging nanotechnology, the precious metal clusters such as Au, Ag and Cu NMs have emerged with different functional agents toward biomedical applications. Compared with traditional fluorescent molecules, the precious metal clusters have the advantages of high optical stability, easy regulation of shape and size, and multifunctionalization. In addition, NMs possesses strong photoluminescent properties with good photostability, high release rate and sub-nanometer size. They could be treated as fundamental agents in bioimaging usability. This review summarizes the recent advances in bioimaging utilization, it conveys that metal clusters refer to Au, Ag, and Cu fluorescent clusters and could provide a generalized overview of their full applications. It includes optical property measurement, precious metal clusters in bioimaging systems, and a rare earth element-doped heterogeneous structure illustrated in biomedical imaging with specific examples, that provide new and innovative ideas for fluorescent NMs in the field of bioimaging usability.